La formación continua del docente de bachillerato de ciencias experimentales, estudio realizado en la institución educativa del cantón Rocafuerte, provincia de Manabí. Ecuador. Periodo lectivo 2019 -2020 - Pin Vega, José Xavier (2020)
A study was carried out whose purpose was to analyze the main continuing education needs of teachers of the General Unified Baccalaureate - BGU in educational institutions in the country, who teach in subjects related to experimental sciences, a methodological design with a qualitativequantitative approach was used Descriptive, non-experimental, the applied methods were: inductive, deductive, analytical, synthetic, and hermeneutical. The techniques used were bibliographic and field research, in this study 10 teachers from BGU of the Educational Unit participated, to whom a questionnaire was applied as a data collection instrument. The results show that the needs for teacher training are based on the fact that they have a third and fourth level professional profile, however, most have degrees related to other professions, therefore, they do not have initial training and Continues in teaching. It is concluded that despite the fact that the professional titles of the teachers are concatenated with the subjects that they teach, this does not ensure that they have the pedagogical, didactic and curricular tools of a teacher training.